(untitled) (Journal of Economic Research & Business Administration, 2016)
The pricing of the bank must keep in mind the activities of competitors. Therefore, the determination of prices at the level of price competition is a common method, although this type of retail pricing is considered to be simple. So it is possible to determine the complexity of the market entry of new banks - participants, as well as price limit market leaders makes it possible to maintain an optimum rate of return of many banks.